A comunicação publicitária nas instituições financeiras para o segmento de alta renda - Noronha, Montresor, Paulo Eduardo (2007)
This research investigates how four of the largest banks operating in Brazil - Bradesco, Itaú, Citibank and BankBoston - use communication to seduce high-income audiences. The goal is to define what are the appeals and values ​​used in television commercials and to understand why movies are so similar in persuasion arguments. The importance of this research is defined as a result of the strong presence of banks in the TV environment and the fact that the main banks in Brazil have launched sub-brands in a short time, a feature widely used by industry with brand extensions, to meet a High income market estimated at 2 million people. This is a new theme and still little explored in the gym. The methods used were content analysis, which verified the arguments of TV commercials and bibliographic research, which provided the necessary ballast for the definition of the problem and based the study structure. The main results of the research presented the conversion of two trends; The first comes from the new values ​​that are blowing from society, especially the high-income people in Brazil. They have introduced new forms of consumption that are much more tied to emotions. The ostentation and consumption of sophisticated products as a synonym for status and power continue and possibly should continue to exist, but it is now noted that at least part of the Brazilian elite seeks to differentiate itself by subjective values. The basic values ​​of society such as family relationships, appreciation of simple things and better use of time are back. On the other hand, the second trend is marketing. With the commoditization of products and services, companies seek to differentiate themselves by brand and to make the connection with consumers, emotional arguments are used. In fact, to manipulate consumers, the most effective way is through emotion. It can also be said that to break the mental block that consumers erect due to the bombardment of messages they receive daily, the way is to entertain, to thrill. Coupled with all this, banks are praying that society has a negative image and have been working to minimize this perception: through their advertising messages they want to become more sympathetic, humane. When these movements come together - that of society valuing "being rather than having" and banks wanting to humanize themselves and using approaches emotional in their communication - it is easy to understand the similarity of arguments. But won't the lack of differentiation continue to bring commoditization of products and services to commoditization of communication and make it fail to fulfill one of its key roles of making an advertiser different from its competitors? (AU)